A Study on the Concept of Employees Customer Orien-tation and its Impact on Competence Development - Madhavi, Thaya; Mehrotra, Rajesh (International Journal of Engineering and Technology, 2018)
It is thought world over that customer orientation of employees needs to corporate success. It constitutes the major element of customer service thrown open by customer oriented service personnel to decide upon the great success of the business firm. Customer oriented service personnel are bestowed with communication, technical, problem solving skills, personality traits and commitment. Anticipating customer wishes and these in advance, and to act accordingly by customer oriented service personnel is a pivotal factor for the progress of an organization. This paper intends to study the concept of operational level employees orientation towards customers and its implication for competence development.